A STUDY ON THE ABILITY IN WRITING FORMAL INVITATION LETTER BY THE SECOND YEAR STUDENTS OF SMA NEGERI 2 TEBING TINGGI (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This descriptive research aimed to find out the ability level of the second-year students of SMA Negeri 2 Tebing Tinggi in writing a formal invitation letter. The subjects of this study were the second-year students of SMA Negeri 2 Tebing Tinggi who were selected by using the cluster random sampling technique. 25 students employed in this study used the Writing Test. The results of the data analysis showed that the mean score of the students` ability in writing a formal invitation letter was 67.48. It can be stated that the ability of the second-year students of SMA Negeri 2 Tebing Tinggi in writing a formal invitation letter was adequate category level. Based on the result of the students’ ability in each writing aspect, the lowest score was in the mechanics' aspect and the highest score is in the organization aspect.Key Words: Study, Writing Ability, Formal Invitation Letter